High Prevalence but Insufficient Treatment of Iron-Deficiency Anemia in Patients with Inflammatory Bowel Disease: Results of a Population-Based Cohort. (30th July 2012) - Ott, Claudia; Liebold, Anne; Takses, Angela; Strauch, Ulrike G.; Obermeier, Florian
Abstract : Background . Iron-deficiency anemia is described to be a common problem in patients with inflammatory bowel disease (IBD), which is frequently associated with a reduced quality of life. Therefore, the aim of this study is to assess the prevalence of iron deficiency anemia in a population-based cohort at time of first diagnosis and during the early course of the disease. Methods . As far as available, lab values of patients registered in the population-based "Oberpfalz cohort" were screened. In anemic patients, we further investigated all laboratory results to differentiate between iron deficiency and other reasons for anemia. All patients with any kind of anemia were interviewed separately according to symptoms of iron-deficiency anemia and administration of iron. Results . In total, we evaluated hemoglobin values of 279 patients (183 Crohn's disease, 90 ulcerative colitis, and 6 indeterminate colitis). Lab data which allowed further differentiation of the type of anemia were available in 70% of anemic patients, in 34.4% values of iron, ferritin and transferrin saturation had been measured. At time of first diagnosis, an iron-deficiency anemia was diagnosed in 26 of 68 patients with anemia (38.2%, 20 CD, 4 UC, and 2 IC patients), but only 9 patients (34.6%) received subsequent iron therapy. After one year, 27 patients were identified to have an iron-deficiency anemia (19 CD, 8 UC), 20 of them were treated with iron (71.4%). Of 9 patients with proven iron-deficiency anemia at time of first diagnosis and subsequent administration of iron, 5 (55.5%) had iron-deficiency anemia despite permanent treatment after one year. In total, 38 patients (54.3%) did not receive any iron substitution at all despite of proven iron-deficiency anemia, and only 13 patients of 74 patients were treated with intravenous iron (17.6%). Conclusion . We found a high prevalence of iron-deficiency anemia at different points during the early course of disease in this population-based cohort of IBD patients. Surprisingly, only in one-third of patients with proven anemia, further diagnostic approach was undertaken. Even patients with diagnosed iron-deficiency anemia were infrequently and inconsequently treated with iron preparations, despite the high impact on quality of life.